Kepuasan Pelanggan Terhadap Pelayanan Service Mesin Cetak Kyocera Di PT Abirama Mulia Persada Dengan Metode Customer Satisfaction Index (CSI) - Hakim, Lukman Nul (Media Teknologi dan Informatika, 2025)
Customer satisfaction and trust are the main issues in every unit operating in the service sector. However, achieving customer satisfaction is not easy because many factors influence achieving this level of satisfaction. The quality of service provided is one of the key factors. in consumer considerations regarding the level of perceived satisfaction. The purpose of this writing is to evaluate the level of customer satisfaction. PT. Abirama Mulia Persada This writing aims to evaluate the perceived level of consumer satisfaction with the company's services and performance and determine priority service criteria. The Customer Satisfaction Index (CSI) method is applied to assess the level of customer satisfaction. Based on the research results, it is known that consumers consist of men and women with an age range between 21 years and 31 years, totaling 34 people, 16 people aged 31 to 41 years, 14 people aged 41 to 51 years, vulnerable respondents aged 41 to 51 years. Respondents aged 51 years to 61 years were 14 people, respondents aged 61 years to 71 years were 3 people. The consumer level for PT Abirama Mulia Persada based on CSI was 79.68%, Cronbach Alpha (a) for service quality was 0.786 and Cronbach Alpha (a) for expectations and performance received a value of 0.688, which can be interpreted as being very satisfied with the service at PT Abirama Mulia Persada. This test uses SPSS Statistics 26 software.